Green chemistry : fundamentals and applications - Ameta, Suresh C.; Ameta, Rakshit (Apple Academic Press, Inc., 2013)
This book highlights the potential and scope of green chemistry for clean and sustainable development. Covering the basics, the book introduces readers to the need and the many applications and benefits and advantages of environmentally friendly chemical practice and application in industry. The book addresses such topics as ecologically safe products, catalysts and solvents, conditions needed to produce such products, types of chemical processes that are conducive to green chemistry, and much more.
Keywords: Green chemistry.; elektronické knihy; electronic books